2001
DOI: 10.1128/aac.45.1.243-251.2001
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of Trovafloxacin against Bacteroides fragilis in Mixed Culture with either Escherichia coli or a Vancomycin- Resistant Strain of Enterococcus faecium Determined by an Anaerobic Time-Kill Technique

Abstract: To determine the efficacy of trovafloxacin as a possible treatment for intra-abdominal abscesses, we have developed an anaerobic time-kill technique using different inocula to study the in vitro killing of Bacteroides fragilis in pure culture or in mixed culture with either Escherichia coli or a vancomycin-resistant strain of Enterococcus faecium (VREF). With inocula of 5 ؋ 10 5 CFU/ml and trovafloxacin concentrations of <2 g/ml, a maximum observed effect (E max ) of >6.1 (log 10 CFU/ml) was attained with all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 29 publications
2
21
0
Order By: Relevance
“…The presence of the E. coli ATCC 25922 and VA 6886 strains reduced the killing activity of moxifloxacin against the B. fragilis strains investigated in the in vitro PK/PD model. This observation is supported by earlier results obtain with trovafloxacin (Stearne et al, 2001). Furthermore, protection of B. fragilis against the activity of metronidazole by Enterococcus faecalis has also been observed (Nagy & Földes, 1991).…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…The presence of the E. coli ATCC 25922 and VA 6886 strains reduced the killing activity of moxifloxacin against the B. fragilis strains investigated in the in vitro PK/PD model. This observation is supported by earlier results obtain with trovafloxacin (Stearne et al, 2001). Furthermore, protection of B. fragilis against the activity of metronidazole by Enterococcus faecalis has also been observed (Nagy & Földes, 1991).…”
Section: Resultssupporting
confidence: 80%
“…Nagy & Földes (1991) reported that metronidazole was inactivated by a cell extract of E. faecalis. However, inactivation of trovafloxacin by Enterococcus faecium was not described (Stearne et al, 2001). antimicrobial agent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Female specific-pathogen-free BALB/c mice (Charles River, Maastricht, The Netherlands) weighing 20 to 25 g were used throughout the study. The cecal contents of male specific-pathogen-free Swiss mice (Charles River) were used for the production of autoclaved cecal contents as preciously described (24). All animals received water and food ad libitum.…”
Section: Methodsmentioning
confidence: 99%
“…The MICs of trovafloxacin and moxifloxacin were determined using the standard broth microdilution method and inocula of 10 5 CFU/ml as previously described (24).…”
Section: Methodsmentioning
confidence: 99%